Efektivitas Penggunaan Media Interaktif Wordwall pada Pembelajaran Matematika Pembagian Bilangan Cacah Kelas 3 di Sekolah Dasar - Namira Alfia Hikma; Zahra Marta Hafidzah; Kowiyah Kowiyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to measure the effectiveness of using the interactive media Wordwall in enhancing third-grade students' understanding of the concept of division of whole numbers. The subjects of this study consist of 24 students. The method used in this research is quantitative with an experimental design, which includes measuring the effectiveness of the interactive media Wordwall in teaching whole number division to third-grade students. Data were collected through pretests and posttests administered to one class to assess changes in students' learning outcomes before and after the implementation of the interactive media. The use of interactive learning tools like Wordwall can stimulate students' interest and motivation in learning. Activities in the form of games and quizzes demonstrate success in learning, as evidenced by the improvement in students' scores after participating in the learning process. The posttest scores of the students were higher compared to their pretest results, and the average score of the third grade also increased, from 49.1 to 80. This learning media is capable of capturing students' attention and facilitating their understanding, thereby accelerating and enhancing their learning outcomes. Overall, the application of the interactive media Wordwall has a positive impact on students' learning results and their active participation in the classroom.